A bizarre Eocene dasyatoid batomorph (Elasmobranchii, Myliobatiformes) from the Bolca Lagerstätte (Italy) reveals a new, extinct body plan for stingrays - Marramà, Giuseppe (Sci Rep, 2019)
In the last few years, the detailed revision of the Eocene cartilaginous fishes (Chondrichthyes) from the Bolca Lagerstätte (Italy) has provided new insights into the fish biodiversity of the western Tethys. The morphological analysis of three previously undescribed specimens from the Pesciara deposit of Bolca revealed the existence of a new stingray taxon, †Lessiniabatis aenigmatica gen. et sp. nov., which is unique among the myliobatiform batoids in having the following unique combination of characters: low number of vertebrae posterior to the pelvic girdle (65–68); thoracolumbar synarcual extending backward beyond the pelvic girdle; tail extremely short not protruding from the posterior edge of the pectoral disc; radials proximally fused to each other; pelvic girdle extremely small and strongly arched; dorsal and caudal fins absent; tail stings and cartilaginous tail rod absent; and teeth of dasyatoid morphology with smooth enameloid surface. The phylogenetic analysis suggests that †Lessiniabatis gen. nov. is deeply nested within the benthic stingrays (Dasyatoidea) representing the sister to all dasyatids and potamotrygonids. Its unique anatomy clearly reveals the existence of a new hitherto unknown body plan experimented by benthic stingrays, whose evolution can be possibly linked to the adaptive fish radiation in the aftermath of the end-Cretaceous extinction.